Research of the relationship between the internationalization of labor resources and their competitiveness - Sikorska, Małgorzata; Pererva, P. G. (Харківський національний університет внутрішніх справ, 2021)
The international competitive environment in the labor market is the result and conditions of interaction of a large number of multicultural subjects of the labor market, which determines the corresponding aggregate level of economic competition and the possibility of the influence of individual economic agents, including foreign entities, on general market situation.
Keywords: labor resources; internationalization; competitiveness; industrial enterprises